بررسی تأثیرات تخریبی و التهابی غلظت‌های مختلف اوژنول در ایجاد تاندونیت تجربی زردپی آشیل در رت - امیرحسام طرقبه; محمد مهدی مولایی; احسان اله سخائی; رضا خیراندیش; پوریا محمدی (مجله دانشگاه علوم پزشکی سبزوار)
Introduction: Tendon injuries are a significant challenge in veterinary medicine, often resulting from repetitive stress or overuse. Traditional methods for developing experimental tendon injury models, such as utilizing collagenase enzyme, face limitations including high costs and restricted availability. This study aims to investigate the destructive and inflammatory effects of different concentrations of eugenol in inducing experimental Achilles tendonitis in rats.Materials and Methods: This research involved six groups of Wistar laboratory rats (one control group and five experimental groups). The experimental groups received varying concentrations of eugenol (diluted in DMSO) in volumetric ratios ranging from 4:1 to 64:1, administered via direct injection into the Achilles tendon to assess local effects.Results: Macroscopic and histopathological assessments revealed that eugenol could induce tendon degradation and inflammation in a concentration-dependent manner. Higher concentrations caused more severe collagen fiber degradation and inflammatory responses, while lower concentrations produced more controlled damage.Conclusion: Eugenol, as a natural compound, effectively induces controlled degradation and inflammation in tendons, presenting a cost-efficient alternative to collagenase for tendon injury modeling. These findings contribute to innovative therapeutic approaches in veterinary medicine and reduce dependence on expensive imported materials.